MENERJEMAHKAN KEMASLAHATAN DALAM PUTUSAN (Studi Terhadap Putusan Verstek Ekonomi Syariah di Pengadilan Agama Sijunjung) - Aprina Chintya (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
The authority to adjudicate shari'ah economic cases has existed since 2006 but the Sijunjung Religious Court will only accept shari'ah economic cases in 2021. The decision was handed down in a verstek and inkracht manner, but Defendant did not carry out the decision voluntarily, so Plaintiff can submit an execution to the Sijunjung Religious Court. It's just that, if the guarantee is in the form of a fiduciary and has been transferred, then the decision that has been handed down by the judge is not carried out. Meanwhile, if the Plaintiff submits an execution and it turns out that the execution cannot be carried out, then this judge's decision does not benefit the Plaintiff. The type of research used is normative-empirical legal research with a qualitative approach. Primary data sources were obtained from sharia economic judges at the Sijunjung Religious Court. While secondary data sources, the authors obtained documentation data of the Sijunjung Religious Court, the Case Tracing Information System (SIPP) of the Sijunjung Religious Court. Techniques in data collection used in this study were interviews and documentation. The data analysis used in this study is an interactive model analysis from Miles and Huberman which divides the analysis into three parts, namely data reduction, data presentation, and drawing conclusions or data verification. Based on the research that has been done, the judge is the central point in decision-making. A good legal decision can be seen in the legal considerations. The legal considerations of the decision reflect the depth of the decision which is loaded with principles, theories, and legal arguments. In the absence of appeals and executions submitted by the parties, it shows that the verstek decision on the simple shari'ah economic lawsuit at the Sijunjung Religious Court has benefited the litigants.